PENERAPAN PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI TK NEGERI PEMBINA SEMARANG - Ellya Rakhmawati; Desi Maulia; Tri Suyati; Agus Suharno (Jurnal Psikologi Integratif, 2019)
The implementation of character education for students at school is done through various ways and is adjusted to condition and environment of the school. The researchers want to find out the implementation done by educators or caregivers of school institution sustainably to observe changes on habits and attitudes of the students completely. The implementation of character education of early children at Pembina Public Kindergarten Semarang is done qualitatively by using descriptive method. The participants are 40 children of B2 and B3 groups, 4 kindergarten teachers, and the principal. The instruments of the research are observation, interview, and documentation. Findings show that character education at the kindergarten can be implemented through habituation in daily life activities. The kindergarten becomes pilot project to promote character education in Semarang city. Varieties of characters to be developed at the kindergarten are taken based on its vision. Character education of Pembina Public Kindergarten Semarang has been lasting for 9 years by bringing positive impacts for the students, school, and parents.